Integrating asthma management and care in Maryland Head Start Programs: A qualitative assessment of opportunities and needs. (December 2019) - Ruvalcaba, Elizabeth; Callaghan-Koru, Jennifer; Rand, Cynthia S.; Eakin, Michelle N.
Highlights: Asthma care can be integrated into Head Start with supportive infrastructure. Integrated HS asthma care programs will need to address regional barriers. HS programs actively engage on health and have trusting family relationships. Communication pathways between HS, families, and PCPs need strengthening. Families have interest in peer education for ongoing asthma education/support. Abstract: Purpose: To understand the role of Maryland Head Start (HS) programs in asthma care and identify resources and needs to improve health outcomes. Methods: A qualitative needs assessment was conducted with Maryland HS staff (n = 35) and parents/caregivers of enrolled children with asthma (n = 16) from all 14 grantee programs in Maryland. Focus group discussions and interviews addressed strengths and challenges in current asthma control and opportunities for integration of an asthma care program into HS services. Transcripts were thematically analyzed using a modified Framework approach. Results: HS programs actively communicate with families about asthma management and facilitate communication between families and primary care providers (PCPs). Both HS staff and families reported a strong trusting relationship allowing HS staff to provide asthma management support. HS needs strong linkages with supportive services and PCP offices to engage families, address environmental triggers, and educate staff. While families across the state report interest in peer education on asthma through HS, there were some region-specific asthma care barriers for urban and rural programs. Conclusion: This needs assessment confirmed interest among all stakeholders in integrating asthma care through HS and identified communication strategies, supportive infrastructure, and addressing regional access to care as key elements for program design.